Screening of Lymphoma Radiotherapy-Resistant Genes with CRISPR Activation Library - Luo BH; Huang JQ; Huang CY; Tian P; Chen AZ; Wu WH; Ma XM; Yuan YX; Yu L (Dove Medical Press, 2023)
Bi-Hua Luo,* Jian-Qing Huang,* Chun-Yu Huang, Pan Tian, Ai-Zhen Chen, Wei-Hao Wu, Xiao-Mei Ma, Yue-Xing Yuan, Lian Yu Department of Hematology, Longyan First Hospital Affiliated Fujian Medical University, Fujian, People's Republic of China*These authors contributed equally to this workCorrespondence: Lian Yu, Department of Hematology, Longyan First Hospital Affiliated Fujian Medical University, No. 105 of Jiuyibei Road, Xinluo District, Fujian, 364000, People's Republic of China, Tel +86 13859572936, Email yulian_ly@126.comObjective: The objective of this study was to screen lymphoma radiotherapy-resistant genes using CRISPR activation (CRISPRa).Methods: The Human CRISPRa library virus was packaged and then transfected into lymphoma cells to construct an activation library cell line, which was irradiated at the minimum lethal radiation dose to screen radiotherapy-resistant cells. Radiotherapy-resistant cell single-guide RNA (sgRNA) was first amplified by quantitative polymerase chain reaction (qPCR) in the coding region and then subject to next-generation sequencing (NGS) and bioinformatics analysis to screen radiotherapy-resistant genes. Certain radiotherapy-resistant genes were then selected to construct activated cell lines transfected with a single gene so as to further verify the relationship between gene expression and radiotherapy resistance.Results: A total of 16 radiotherapy-resistant genes, namely, C20orf203, MTFR1, TAF1L, MYADM, NIPSNAP1, ZUP1, RASL11A, PSMB2, PSMA6, OR8H3, TMSB4Y, CD300LF, EEF1A1, ATP6AP1L, TRAF3IP2, and SNRNP35, were screened based on the NGS results and bioinformatics analysis of the radiotherapy-resistant cells. Activated cell lines transfected with a single gene were constructed using 10 radiotherapy-resistant genes. The qPCR findings showed that, when compared with the control group, the experimental group had significantly up-regulated mRNA expression of MTFR1, NIPSNAP1, ZUP1, PSMB2, PSMA6, EEF1A1, TMSB4Y and TAF1L (p < 0.05). No significant difference in the mRNA expression of AKT3 or TRAF3IP2 (p > 0.05) was found between the two groups (p > 0.05).Conclusion: The 16 genes screened are potential lymphoma radiotherapy-resistant genes. It was initially determined that the high expression of 8 genes was associated with lymphoma radiotherapy resistance, and these genes could serve as the potential biomarkers for predicting lymphoma radiotherapy resistance or as new targets for therapy.Keywords: lymphoma, radiotherapy resistance, gene, CRISPR/Cas9